Mindfulness, rejection sensitivity and resilience in patients with thalassemia: a survey in Southeastern Iran - Ghonchehpour, Asma; Tirgari, Batool; Dehghan, Mahlagha; Ahmadi, Atefeh; Azizzadeh Forouzi, Mansooreh (Frontiers in Psychiatry, 2025)
BackgroundThalassemia, due to its chronic nature, predisposes patients to various psychological issues, including rejection sensitivity, and can negatively impact resilience, thereby reducing quality of life. Mindfulness, as a psychological construct, has been shown to enhance emotional regulation and resilience, and may serve as a mediating factor in reducing rejection sensitivity and promoting resilience. This study aimed to investigate mindfulness and its correlation with rejection sensitivity and resilience in patients with thalassemia.MethodsThis cross-sectional descriptive-correlational study involved 143 patients with thalassemia attending the Thalassemia Center in Kerman, Iran, during the year 2022-2023. Patients were asked to fill demographic and disease-related information form, the Freiburg Mindfulness inventory Short Form (FMI-SF), the Adult Rejection Sensitivity Questionnaire (A-RSQ), and the Conner-Davidson Resilience Scale. Data were analyzed using SPSS V.25.ResultsThe results showed a negative and significant correlation between mindfulness and rejection sensitivity (p = 0.001, r = -0.28). There was a positive and significant correlation between mindfulness and resilience (p<0.001, r = 0.48). Additionally, rejection sensitivity had a negative significant correlation with resilience (p < 0.001, r = -0.32). Linear regression analysis was used to assess the predictive relationships between variables. It indicated that mindfulness significantly predicted resilience (p < 0.05), while there was no significant predictive relationship between mindfulness and rejection sensitivity (p=0.05).ConclusionThis study found that mindfulness levels are associated with resilience and rejection sensitivity in patients with thalassemia. According to the results of the present study, tailoring interventions to effectively support thalassemia patients in managing rejection sensitivity and enhancing resilience could be beneficial, particularly when combined with mindfulness practices. However, further research is necessary to confirm their clinical effectiveness.